Symmetry Dimension in Obsessive-Compulsive Disorder: Prevalence, Severity and Clinical Correlates - Vellozo, Aline P. [UNESP] (2021)
Background: Obsessive-compulsive disorder (OCD) is a very heterogeneous condition that frequently includes symptoms of the symmetry dimension (i.e., obsessions and/or compulsions of symmetry, ordering, repetition, and counting), along with aggressive, sexual/religious, contamination/cleaning, and hoarding dimensions. Methods: This cross-sectional study aimed to investigate the prevalence, severity, and demographic and clinical correlates of the symmetry dimension among 1001 outpatients from the Brazilian Research Consortium on Obsessive-Compulsive Spectrum Disorders. The main assessment instruments used were the Dimensional Yale-Brown Obsessive-Compulsive Scale, the Yale-Brown Obsessive-Compulsive Scale, the USP-Sensory Phenomena Scale, the Beck Depression and Anxiety Inventories, the Brown Assessment of Beliefs Scale, and the Structured Clinical Interview for DSM-IV Axis I Disorders. Chi-square tests, Fisher's exact tests, Student's t-tests, and Mann-Whitney tests were used in the bivariate analyses to compare patients with and without symptoms of the symmetry dimension. Odds ratios (ORs) with confidence intervals and Cohen's D were also calculated as effect size measures. Finally, a logistic regression was performed to control for confounders. Results: The symmetry dimension was highly prevalent (86.8%) in this large clinical sample and, in the logistic regression, it remained associated with earlier onset of obsessive-compulsive symptoms, insidious onset of compulsions, more severe depressive symptoms, and presence of sensory phenomena. Conclusions: A deeper knowledge about specific OCD dimensions is essential for a better understanding and management of this complex and multifaceted disorder.